1994
DOI: 10.1007/bf00591052
|View full text |Cite
|
Sign up to set email alerts
|

Alternative laparoscopic management of perforated peptic ulcers

Abstract: Surgery--namely, suture closure-is still the treatment of choice for perforated peptic ulcers, despite the proven efficacy of Taylor's conservative approach. Such conservative management, however, has been proven less effective in high-risk patients and those with perforations more than 12 h old. Here we suggest alternative laparoscopic treatments for perforated peptic ulcers. We have treated laparoscopically six patients (one F, five M; mean age 57.6 years; range 31-81 years); the mean duration of the operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 14 publications
2
22
0
1
Order By: Relevance
“…Lavage is an adequate measure to counteract the negative effects of peritonitis, which form the major cause of morbidity and mortality in these patients. Some investigators [32] even obtained very satisfactory results performing only laparoscopic lavage and drainage in combination with a conservative Taylor method, confirming the earlier-reported important role of lavage in the perforation management [11]. Our 100-patient series matches favorably with the Hong Kong consecutive series of 100 cases operated by means of either omental patch repair (n ‫ס‬ 44) or suture patch repair (n ‫ס‬ 35) or fibrin glue repair (n ‫ס‬ 21) [25].…”
Section: Discussionsupporting
confidence: 91%
“…Lavage is an adequate measure to counteract the negative effects of peritonitis, which form the major cause of morbidity and mortality in these patients. Some investigators [32] even obtained very satisfactory results performing only laparoscopic lavage and drainage in combination with a conservative Taylor method, confirming the earlier-reported important role of lavage in the perforation management [11]. Our 100-patient series matches favorably with the Hong Kong consecutive series of 100 cases operated by means of either omental patch repair (n ‫ס‬ 44) or suture patch repair (n ‫ס‬ 35) or fibrin glue repair (n ‫ס‬ 21) [25].…”
Section: Discussionsupporting
confidence: 91%
“…It has been demonstrated in prospective randomized trials that laparoscopic appendectomy is superior or at least does not differ compared to open appendectomy in terms of postoperative complications, hospital stay, and recovery [1,11]. Urbano et al further demonstrated that laparoscopic surgery of perforated peptic ulcers is simple, rapid, and followed by a quick recovery [13]. In contrast to these results, Eypasch et al reported higher morbidity after laparoscopic treatment of perforated peptic ulcer than after a conventional approach [5].…”
Section: Discussionmentioning
confidence: 98%
“…Some authors reported successful treatment of inflammatory processes like appendicitis, Crohn's disease, perforated peptic ulcer, or diverticular disease [1,3,9,11,13]. Furthermore, laparoscopic surgery appears to be feasible in patients with abdominal sepsis without increasing postoperative morbidity and mortality [6].…”
mentioning
confidence: 97%
“…If the ulcer is already covered by omentum, the authors generally restrict themselves to peritoneal drainage and lavage, since they consider it the most important part of any intervention. Other techniques of ulcer repair are: suturing with single stitches [8,30], closure with gelatine sponges and fibrin glue [11,12], sutured or stapled omental patch repair [10,11,12,17,18,21,22,23,24,26,27] and gastroscopyaided insertion of the ligamentum teres hepatis or omental plug [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…There is still, however, disagreement as to the relative merits of laparoscopic ulcer repair. Laparoscopic techniques such as omental patch repair, gelatine sponge, fibrin glue [11,12] and gastroscopy-assisted methods [19,20] are time consuming and require extended surgical skills with respect to suturing and knotting techniques [5,11,12,18,19,21,22,23,24,25,26,27].…”
Section: Introductionmentioning
confidence: 99%